Gender Effects in Discipline Arbitration: Evidence from British Columbia - Bemmels, Brian (Academy of Management Journal, 1988)
The article deals with a study which presents evidence that arbitrators treat women employees more leniently than men in discipline grievance situations. A discussion is presented about the implications of this bias for management, unions, and the institution of grievance arbitration. The author looks at options to remedy gender biases in arbitration and justice procedures in organizations. Psychological and social factors influencing arbitrators' views of female employees and sex role in the workplace are discussed.